(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The health sector in rural India faces numerous challenges, including inadequate healthcare facilities, a shortage of qualified health personnel, and low awareness of health issues among the population. As a result, rural communities often resort to traditional and ineffective remedies, leading to adverse health outcomes. This paper discusses the concept of health branding and its critical importance in rural India. By analyzing existing gaps in healthcare delivery and suggesting branding strategies, this paper aims to highlight how effective health branding can improve awareness, accessibility, and the overall quality of healthcare services in rural regions.